Manajemen Pembelajaran pada Prodi PGMI dalam Meningkatkan Kecerdasan Spiritual Mahasiswa di Institut Daarul Qur’an Jakarta - Reza Rahmadani; Ahmad Zain Sarnoto; Syamsul Bahri Tanrere (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
This research uses a qualitative method with a case study approach through interviews, observation, and documentation to obtain in-depth data related to the implementation of learning management and its influence on spiritual intelligence. Using a descriptive analysis approach, the author identified findings in the field related to learning management in an effort to improve students' spiritual intelligence starting from curriculum planning, organising resources, controlling, supervising, and evaluating to run the learning process well. The results showed that the implementation of learning management in the PGMI study programme at Institut Daarul Qur'an Jakarta significantly contributed to improving students' spiritual intelligence. Programmes such as the Daqu Method and Tahsin & Tahfiz Intensive courses for students, as well as the integration of Islamic values in the curriculum are the main supporting factors. However, the biggest challenge faced is the different educational backgrounds of prospective students which affects their readiness in developing spiritual intelligence. To overcome this, the institute implemented an adjustment strategy through remedial programmes and more intensive personal guidance.